Gender-sensitive considerations of prehospital teamwork in critical situations - Zimmer, Matthias; Czarniecki, Daria Magdalena; Sahm, Stephan (Philosophy, ethics, and humanities in medicine : PEHM, 2024)
Teamwork in emergency medical services is a very important factor in efforts to improve patient safety. The potential differences of staff gender on communication, patient safety, and teamwork were omitted. The aim of this study is to evaluate these inadequately examined areas. A descriptive and anonymous study was conducted with an online questionnaire targeting emergency physicians and paramedics. The participants were asked about teamwork, communication, patient safety and handling of errors. Seven hundred fourteen prehospital professionals from all over Germany participated. A total of 65.7% of the women harmed a patient (men 72.9%), and 52.6% were ashamed when mistakes were made (men 31.7%). 19.0% of the female participants considered their communication skills to be very good, compared to 81% of the men. More women than men did not want to appear incompetent (28.4%, 15.5%) and therefore did not speak openly about mistakes. Both genders saw the character of their colleagues as a reason for poor team communication (women 89.4%, men 84.9.%). Under high stress, communication decreased (women 35.9%, men 31.0%) and expression became inaccurate (women 18.7%, men 20.1%). Team communication problems and teamwork in rescue services are independent of gender. Women seem to have more difficulty with open communication about mistakes because they seem to be subject to higher expectations. Work organization should be adapted to women's needs to enable more effective error management. We conclude that it is necessary to promote a positive error and communication culture to increase patient safety.